(3GdBOGH GdTQYjI hGdeUGdM GdeQYjIs - (3GHf oerapdM , eMeO Hf eadM Hf eMeO Hf eaQL, CHh YHO Gddg, TeS GdOjf GdebOSj GdQGejfj Ke GdUGdMj,J (B763 (3g` s
(3ChdgG (B:s
(3CeG HYO agPG cJGH jTJed Ydi LedI cKjQI ef GdBOGH GdTQYjI hGdeUGdM GdeQYjI jMJGL Edi eYQaJI Gh eYQaI cKjQ efg cd YGde hYGHO hcd eSde s
(3BNQgG (B:s
(3hGNJGQ GdTjN Jbi GdOjf Gf GdeQGO HGdMQa GdcdeI ShGA cGfJ GSekG Gh aYdkG Gh MQakG GUWdGMkG hGUHM HGdLQ GdePchQ abO GSJYedg GdTGQY gfG hGddg SHMGfg hJYGdi GYde Hefg haVdg hcQeg Je GdLRA GdChd ef cJGH GdBOGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B44s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B42s
Keywords: (3Gdabg GdESdGejs